Creating theory: Encouragement for using creativity and deduction in qualitative nursing research - Bergdahl, Elisabeth (Nursing philosophy, 2023)
Texts about theory in nursing often refer to theory construction by using inductive methods in a rigid way. In this paper, it is instead argued that theories are created, which is in line with most philosophers of science. Theory creation is regarded as a creative process that does not follow a specific method or logic. As in any creative endeavour, the inspiration for theory creation can come from many sources, including previous research and existing theory. The main idea put forward is that deductive qualitative research approaches should play a key role in theory creation. Furthermore, there is a need to differentiate between theory creation and theory justification. A model that emphasizes the creative aspects of theory creation and theory justification using qualitative approaches is presented. The model suggests that knowledge development is a deductive trial-and-error process where theory creation is followed by testing. Scientific theory creation and justification are presented as an iterative process that is deductive in that a testable hypothesis is derived from the theory. If the hypothesis is falsified, then the theory needs modification or might be altogether wrong. Several factors can block the creative process, both in theory development and in finding ways to test a theory in the justification phase. Some of these blockers are the idea of ‘building blocks’ and the inductive view of science often brought forward in nursing. Other blockers include striving for consensus and adherence to existing nursing philosophies and existing theories. Research and knowledge development are creative processes, and following predefined methods is not enough to ensure scientific rigour in qualitative nursing research.